The Usage of Automatic Identification System (AIS) Data for Safety during Navigation - Amirrudin Yaacob; Jaswar Koto (International Journal of Supply Chain Management, 2018)
Estimation of safety on navigation by using safety distance formulation of sea transport is possible with by using data from the Automatic Identification System (AIS). Based on AIS data can be calculated the safety distance and actual distance of the target ship and also closest ship Calculation of safety distance and actual distance of the ship using AIS data closer to the real condition because AIS data provide ship data (time and location) as real-time. This study showed that calculation of safety distance is able to cover all speed more than 5 knots. The results show several ships from 295 total numbers of ships through the Strait of Malacca on 15th November 2013, 8.00 pm until 9.00 pm in danger condition but need to refer to the type of the ship also by using the information from the references website. The ships under the Singapore flag contribute the highest values from the total quantity of the marine traffic on 15th November 2013, 8.00 pm until 9.00 pm follow by Panama, Liberia and Marshall Island. The most high-risk time which danger to the marine transportation and shipping traffic in the Strait of Malacca.